Research on Real Scene Robot 3d Visualization of Historical Architectural Heritage Based on Big Data Objects - Wu, Wei; Ye, Li (Informatica, 2024)
In the era of the rapid development of big data technology, 3D robot technology has been widely used in various aspects such as real scene demonstration and maintenance of historical buildings, and has far-reaching significance in the recording, maintenance and restoration of historical buildings. The development of big data technology makes robot simulation of human beings become a safe, reliable, flexible and convenient design means, which plays a pivotal role in the overall design and development of robots. In this paper, virtual reality technology is used to realize the construction of visual 3D system. Taking a serial robot with six degrees of freedom as an example, the 3D entity modeling is constructed by using the big data object measurement method. This paper constructs a robot model in big data object estimation, and then introduces it into OpenGL through the form transformation of data. On this basis, it integrates with VC++ to construct a robot motion simulation system based on big data VC++. In the experiment of the 3D robot with visualization, because of the low quality of the captured image, the two-dimensional maximum threshold image based on the maximum two times threshold is used to analyze. The experiment proves that based on the big data object, the real robot can make full use of the spatial information of the image, reduce the computing speed, and achieve a good visualization effect in the recording, maintenance and repair of historical architectural heritage, and has certain practical significance.